UNIT COSTS OF INSTRUCTION AT THE UNIVERSITY OF PENNSYLVANIA. - MacLean, H. I. (The Accounting Review, 1934)
Abstract At the University of Pennsylvania, an accounting plan has been developed which fundamentally arrives at a deficit or surplus for each department, which in turn is closed into the general deficit account. One obtains figures upon the instructional salaries, other salaries and wages, and departmental current expense and distribute the general overhead of the various departments upon various bases, so that the cost system, which appears on the surface to be quite an elaborate set-up is in reality very simple. It is realized that budgeted expenses do not necessarily have any relation to the income or receipts of any school or department due to the inter-relationship of the several faculties of instruction. It may be also noted that the budgets of the various departments do not include a charge for the building expense, general expense, or for instruction furnished by other school or departments. Separate budgets are of course prepared under budget administrators for building expense, and the various items finally closed into general university expenses. Later in this paper is a discussion of the method of charging the instructional expenses to the various schools and departments.